PELATIHAN PEMBUATAN COOKIES DARI TEPUNG PISANG MAS DI DESA PAKUAN KECAMATAN NARMADA LOMBOK BARAT - Cicilia, Siska; Pawestri, Setyaning; Alamsyah, Ahmad; Handito, Dody; Kholisah, Mutia Nur; Oktaviana, Sari; Partiwi, Eka (Jurusan Teknik Elektro Universitas Mataram, 2024)
Pakuan is one of the villages located near the Sesaot Protected Forest and is included in the Narmada District, West Lombok. One of the commodity that has the potential to be developed is pisang mas. The communities of Pakuan Village have processed pisang mas into chips and dried bananas. This training aims to provide knowledge to the communities about the diversification of banana processing in the form of banana flour which is processed into cookies. The ingredients and process for making banana cookies are almost the same as wheat cookies. Based on the evaluation at the end of the training, it was discovered that all participants gained knowledge about processed banana mas other than chips and dried banana. Apart from that, participants were able to process the bananas into cookies. Participants took part in the activity stages enthusiastically and were motivated to process pisang mas into flour and cookies.